The Emancipation of the Flesh: The Legacy of Romanticism in the Homosexual Rights Movement - Tobin, Robert (Romanticism on the Net)

(untitled) (Université de Montréal, 2004)
AbstractThe nineteenth-century German homosexual rights movement adopted the rhetoric of the “emancipation of the flesh,” which had its roots in Romanticism. Friedrich Schlegel’s Lucinde (1799) promoted the emancipation of the flesh by calling for a strong female sexuality that would help overcome the tyranny of the conventional bourgeois family. Karl Gutzkow’s controversial novel Wally (1835) harked back to Schlegel as it championed the emancipation of Jews as well as women. Heinrich Hössli, author of Eros, the two-volume apology for male-male love that appeared in 1836 and 1838, clearly read the journals in which the controversies about Wally played out. He and subsequent activists in the homosexual rights movement, particularly Karl Heinrich Ulrichs, drew on these radical Romantic calls for sexual emancipation.